2015
DOI: 10.1128/mbio.02513-14
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Epsilon Toxin Causes Selective Death of Mature Oligodendrocytes and Central Nervous System Demyelination

Abstract: Clostridium perfringens epsilon toxin (ε-toxin) is responsible for a devastating multifocal central nervous system (CNS) white matter disease in ruminant animals. The mechanism by which ε-toxin causes white matter damage is poorly understood. In this study, we sought to determine the molecular and cellular mechanisms by which ε-toxin causes pathological changes to white matter. In primary CNS cultures, ε-toxin binds to and kills oligodendrocytes but not astrocytes, microglia, or neurons. In cerebellar organoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 57 publications
1
86
0
1
Order By: Relevance
“…In line with this idea, it has been shown recently that nascent MS lesions with oligodendrocyte loss, in the absence of the adaptive immune infiltrates, occurred in a patient who tested positive for the Clostridium perfringens type B, indicating that MS might be triggered by an agent cytotoxic to oligodendrocytes 33 . Both type B and D strains of C. perfringens cause a severe demyelinating disease in ruminant animals that is similar to human MS by producing ε-toxin, which specifically targets and kills mature oligodendrocytes in the CNS 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with this idea, it has been shown recently that nascent MS lesions with oligodendrocyte loss, in the absence of the adaptive immune infiltrates, occurred in a patient who tested positive for the Clostridium perfringens type B, indicating that MS might be triggered by an agent cytotoxic to oligodendrocytes 33 . Both type B and D strains of C. perfringens cause a severe demyelinating disease in ruminant animals that is similar to human MS by producing ε-toxin, which specifically targets and kills mature oligodendrocytes in the CNS 34 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, demyelination occurs in very low ETX concentrations (< 0.01nM) 33 at which it has not been established that ETX can form heptamers. We also found that extracellular Ca 2C and intracellular Ca 2C stores were both involved in ETX induced increase in intracellular Ca 2C concentration.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously proposed that a bacterial neurotoxin, epsilon toxin, from the anaerobic gut bacterium, Clostridium perfringens , may play a pivotal role in triggering newly forming MS lesions (Rumah et al, 2013, 2015; Linden et al, 2015). Epsilon toxin (ETX) is a rational candidate MS trigger due to its tropism for the blood-brain barrier (BBB) and for the myelin sheath; both of which are specifically damaged during each MS relapse (Dorca-Arévalo et al, 2008; Rumah et al, 2013; Linden et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Epsilon toxin (ETX) is a rational candidate MS trigger due to its tropism for the blood-brain barrier (BBB) and for the myelin sheath; both of which are specifically damaged during each MS relapse (Dorca-Arévalo et al, 2008; Rumah et al, 2013; Linden et al, 2015). Remarkably, newly forming MS lesions display evidence of BBB breakdown, oligodendrocyte cell death and early microglial activation in the absence of a peripheral inflammatory infiltrate (Barnett and Prineas, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation